Degree of free cash flow leverage. Issue 3 (15th July 2019) - Aharon, David Yecham; Kroll, Yoram; Riff, Sivan
Abstract : Purpose: This paper aims to forgo the conventional (degree of operating leverage) risk measure by replacing elasticity of operating profits with respect to output with elasticity of free cash flow (FCF) with respect to optimal output and by considering exogenous random demand shocks for the firm's products as a source of risk. Design/methodology/approach: The elasticity risk measure accounts for corporate taxes and the cost of bankruptcy. The methodology is selecting optimal level of production investment and capital structure to generate efficient frontier of expected FCF and its risk in terms of its elasticity with respect to output. Findings: The risk measure leads to efficient frontier between expected FCF and its idiosyncratic managerial risk. The model also resolves the empirical debate on the tradeoff between operating and financial leverages. Originality/value: It is the first elasticity risk measure that embodied the impact of future level of capital expenditure, total level of assets and their sensitivity to random shocks in the product market.